Optimization of Planar Antenna Arrays Using the Firefly Algorithm - Yoshimoto, Eduardo; Heckler, Marcos V. T. (Journal of Microwaves, Optoelectronics and Electromagnetic Applications, 2019)
Abstract This paper describes the application of the Firefly Algorithm for the optimization of linear and planar antenna arrays. In order to demonstrate the potential of this technique, three applications are reported. The first one is the synthesis of a radiation pattern with isoflux distribution with a non-uniformly spaced linear array composed of isotropic antennas. The second application is the optimization of a non-uniformly spaced planar array composed of isotropic radiators installed on an 8-U nanosatellite. Finally, the optimization of a 3×3 planar antenna array for beam steering with simultaneous side lobe level control is described, whereby the beamforming coefficients were allowed to assume only discrete values. In the three cases considered, good agreement between the desired (mask) and the optimized patterns has been obtained.